Promoting cultural literacy and community engagement through educational technology: Evidence from the implementation of Go Buya Learning Media - Tri Syamsijulianto; Alvira Pranata (Privietlab, 2026)
This study investigates the effectiveness of the Go Buya digital learning platform in enhancing cultural literacy and civic knowledge among fourth-grade students at MIS Istiqomah Entikong, a school located in the Indonesia–Malaysia border region. A quantitative experimental design with a pre–post methodology was employed, involving 27 student participants. Cultural and civic competencies were assessed using standardized evaluation instruments and analyzed through normality testing, homogeneity testing, paired-sample t-tests, and Wilcoxon signed-rank tests. The findings reveal a steady improvement in student performance, indicated by an increase in mean scores from 61.19 (pretest) to 82.33 (final posttest). While levels of statistical significance varied, all phases demonstrated positive learning gains. The results suggest that integrating interactive, game-based platforms such as Go Buya can strengthen cultural identity, foster community engagement, and support citizenship education, particularly in multicultural learning environments situated in border areas.